Regulation of human tonsillar T-cell proliferation by the active metabolite of vitamin D3. - Nunn, J D (1986)
We have examined the effects of 1,25(OH)2D3 on T-cell populations isolated by buoyant density and E rosetting from human tonsils. Cell proliferation was assessed by measuring the incorporation of 125iododeoxyuridine; interleukin-2 (IL-2) production was measured using an IL-2-dependent cell line, and the number of 1,25(OH)2D3 receptors was measured by whole-cell nuclear association assay. At a concentration of 10(-7) M, 1,25(OH)2D3 inhibited mitogen-induced T-cell proliferation in all E+ T-cell populations. This effect was more pronounced in the cells from the intermediate and high density layers and was reflected both in cell proliferative responses and in relative IL-2 synthesis. By adding the 1,25(OH)2D3 during the course of the mitogen assay, we demonstrated that activation of the T cell precedes the 1,25(OH)2D3-mediated inhibition. Cells that had been preincubated with mitogen in the presence of the 1,25(OH)2D3 were refractory to further stimulation by mitogens. Receptors for 1,25(OH)2D3 could not be detected in unstimulated T cells. However, activation led to the expression of high-affinity receptors for 1,25(OH)2D3. Co-incubation of the cells with mitogen and 1,25(OH)2D3 increased the number of receptors compared with mitogen alone. The effects provide further evidence for the hypothesis that 1,25(OH)2D3 is an important potential modulator of the immune system through its action on T cells. Taking our observations in conjunction with the known capacity of monocytes to hydroxylate the precursor metabolite (and thus synthesize the active form of cholecalciferol), the results support the suggestion that 1,25(OH)2D3 plays a role as a local mediator of mononuclear phagocyte-T cell interaction in human lymphomedullary tissues.